Parameter Fisikokimia dan Analisis Kadar Allyl Disulfidedalam Ekstrak Etanol 70% Bawang Putih (Allium sativum L.)dengan Perbandingan Daerah Tempat Tumbuh Parameter - Prastiwi, Rini; Siska, Siska; Marlita, Nila (Pharmaceutical Sciences and Research, 2017)
Garlic (Allium sativum L.) is one of the medicinal plants that has a potential to be developed to become a traditional medicine. Traditional medicinal products and medicinal plants which have good quality are determined by the quality and safety of the extract. One of many factors that can affect the quality is the growing area. This research aimed to compare the value of physicochemical parameters as well as the levels of compounds responsible for pharmacological activity in ethanol 70% extract of garlic obtained from two growing areas, Bogor and Wonosobo. The test results obtained from garlic extract of Bogor were: compound contents dissolved in water was 62.5684%, compound contents dissolved in ethanol was 10.0779%, essential oils contents was 0.7477%, levels of allyl disulfide was 1.8322%, total ash content was 2.3529%, ash content insoluble in acid was 0.1115%. While the test results obtained from garlic extract of Wonosobo: compound contents dissolved in water was 59.0007%, compound contents dissolved in ethanol was 8.9230%, essential oils contents was 0.3400%, levels of allyl disulfide was 1.6542%, total ash content was 3.0196%, ash content insoluble in acid was 0.4974%. Based on those results, the best quality extract was garlic from Bogor with higher specific parameter values and lower non-specific parameter values.